Investigation of anti-asthmatic potential of Kanakasava in ovalbumin-induced bronchial asthma and airway inflammation in rats. (2nd February 2017) - Arora, Poonam; Ansari, S.H.; Anjum, Varisha; Mathur, Rajani; Ahmad, Sayeed
Abstract: Ethno-pharmacological relevance: Kanakasava is an Indian traditional Ayurvedic formulation containing Datura ( Datura metel ), Vasaca ( Adhatoda vasica ), Dhataki ( Woodfordia fruticosa ) and Grape ( Vitis vinifera ) extracts as major constituents and used to treat pulmonary diseases including coughing, breathing difficulty and asthma. The present study was designed to assess the safety and therapeutic efficacy of Kanakasava against ovalbumin-induced bronchial asthma and related airway inflammation in rats due to lack of evidence based therapeutic efficacy data. Material and methods: Male wistar rats were sensitized with allergen (ovalbumin, 40 mg/rat+aluminum hydroxide, 2.0 mg/rat) and treated orally with standard dexamethasone (2.5 mg/kg, b.w.) or Kanakasava (1.23 and 2.46 ml/kg, b.w.) from day 1 to day 28. Inflammatory markers, including cell counts and cytokines such as interleukins (IL-4, IL-5, IL-1β), tumor necrosis factor (TNF-α), leukotriene (LTD-4), immunoglobulin (IgE), nitric oxide and nitrite levels in both blood and broncheo alveolar lavaged fluid (BALF) were analyzed. Abdominal mesentery was studied histologically for mast cell degranulation, whereas lung functions were investigated by spirometer. Method was also developed to quantify gallic acid and ethyl gallate content in Kanakasava by HPTLC for its quality control. Results: None of the rats exhibited mortality and Kanakasava was found to be safe at the tested doses. Treatment with Kanakasava significantly (P<0.01) reversed elevated levels of IgE, cytokines, nitrites and influx of eosinophils and neutrophils in blood and BALF. These findings were further supported by the significant improvement in lung functions (P<0.01) and suppression (P<0.01) of degranulation of mast cells. The content of gallic acid and ethyl gallate in Kanakasava was found to be 1.94% and 0.98%, respectively. Conclusion: These findings demonstrated the preventive effect of Kanakasava in allergen induced model of asthma providing scientific basis for its traditional use in Ayurveda, since long time. Graphical abstract: